2018
DOI: 10.1111/zsc.12297
|View full text |Cite
|
Sign up to set email alerts
|

The phylogeny of the genus Indoplanorbis (Gastropoda, Planorbidae) from Africa and the French West Indies

Abstract: Indoplanorbis exustus is a freshwater snail known as the intermediate host of various trematode parasites, including different species of the genus Schistosoma. Although its genetic diversity is well described in Asia, the phylogenetic diversity of strains from Africa and Guadeloupe (French West Indies) and their relationship to Asian and South‐East Asian strains remain unknown. To tackle this issue, we sampled individuals from Africa and Guadeloupe, and we computed phylogenetic reconstructions using five mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 23 publications
5
20
0
Order By: Relevance
“…In the latter case, dispersal may occur in clumps of mud stuck to cattle and water buffalo or disperse via water in debris [ 17 ]. Currently, I. exustus is known to be a widely distributed species in tropical and subtropical zones throughout South and Southeast Asia, southern China and across Africa to the French West Indies [ 18 , 19 ]. In addition, seasonal rainfall variations have been shown to influence the distribution of I. exustus in Assam/Bangladesh and both the Southeast Asian mainland and peninsula.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the latter case, dispersal may occur in clumps of mud stuck to cattle and water buffalo or disperse via water in debris [ 17 ]. Currently, I. exustus is known to be a widely distributed species in tropical and subtropical zones throughout South and Southeast Asia, southern China and across Africa to the French West Indies [ 18 , 19 ]. In addition, seasonal rainfall variations have been shown to influence the distribution of I. exustus in Assam/Bangladesh and both the Southeast Asian mainland and peninsula.…”
Section: Introductionmentioning
confidence: 99%
“…A series of investigation into the genetic and phylogenetic variations in I. exustus using mitochondrial DNA sequences has revealed that four to five genetically distinct lineages, clades, were always congruent, suggesting I. exustus may comprise more than one species or, in fact, be a species complex [ 5 , 10 , 17 , 19 ]. It was initially classified as clades existing in north India (Assam and Bangladesh) and Cratonic India (Sri Lanka), ubiquitous in Thailand, the Philippines, and Nepal, Sundaic in Indonesia, as well as Arabian and Malaysian clades [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last few years, DNA sequencing data has been used to study and clarify the evolution of morphological characteristics of ambiguous organisms [ 15 18 ] while genetic studies of land snails using DNA sequence data could be valuable for their identification [ 19 21 ]. The most commonly used genes for genetic analysis in land snails are the mitochondrial cytochrome c oxidase subunit I (COI) and 16S rRNA genes [ 20 , 22 24 ].…”
Section: Introductionmentioning
confidence: 99%